Out of Africa: Complete and partial remissions as a combined outcome in patients with idiopathic membranous glomerulonephritis in Cape Town. Issue 12 (December 2016) - Ameh, Oluwatoyin I; Swanepoel, Charles R; Aderibigbe, Ademola; Kengne, Andre´ P; Okpechi, Ikechi G
Abstract: Aim: Remission outcomes among patients with idiopathic membranous glomerulonephritis is unknown in Africa. We sought to determine remission outcomes in a cohort of South African adult patients with IMGN. Methods: This was a retrospective review of patients with biopsy‐proven IMGN over a 10 year period. Secondary causes of MN were excluded. Demographic, clinical, biochemical and histological records were retrieved for analysis. The trends in biochemical parameters from baseline were determined. The primary outcome was the attainment of a complete or partial remission (CR / PR) at the last follow‐up. Results: Fifty‐six patients met the criteria for inclusion and 43 had subsequent follow‐up care with a median duration of follow‐up of 23.0 (13.0–48.0) months. Sixteen patients (37.2%) were treated with immunosuppression (corticosteroids and cyclophosphamide) and 81.4% received anti‐proteinuric agents. There were no significant differences in demographic and clinical features of patients categorized by immunosuppression (ISP) use. Changes in level of proteinuria and estimated glomerular filtration rate (eGFR) were also not significantly different between the two groups. Eighteen patients (41.9%) reached CR or PR at the last visit. The median times‐to‐remission of patients according to ISP status were similar at 48.6 and 48.7 months respectively ( P = 0.104) while the proportions of patients not reaching CR/PR at 12 and 24 months were 94.6% and 80.8% respectively. Gender and race did not predict remission status ( P > 0.05). Predictors of CR/PR at last visit were eGFR [OR 1.01 (95%CI: 1.00 – 1.02); P = 0.041], and systolic BP (OR 0.97 [95%CI: 0.95 – 0.99); P = 0.036]. Conclusion: Remission outcomes in this African IMGN cohort are delayed and poor. SUMMARY AT A GLANCE: This paper provides unique information on the management of membranous glomerulonephritis in a challenging, developing world environment.